An Investigation of the Effects of Chronic Stress on Attention in Parents of Children with Neurodevelopmental Disorders - Ranganathan, Maharishi; Jacob, Abin; Ashraf, Ashifa Kariveliparambil Mohammed; Kumar, Ganesh J.; Anthony, Madalaimuthu; Vijay, M.; Kumari, Rupashree Brahma (Horizon Research Publishing, 2024)
Prolonged exposure to stress can cause impairments in various brain functions including cognition. Attention is one such important cognitive function that is required for our daily life and work-related activities. Chronic stress can have an impact on attention networks such as alerting, executive control, and orienting. The effects of naturalistic, persistent psychosocial stress on several attention networks were explored in this study. Parents of children with neurodevelopmental disorders (NDD) and parents of children with typical development (TD) were given an attention network test (ANT). Overall the stressed group (M= 564.623, SD= 75.484) was found to have a quicker reaction time in all the target and cue conditions whencompared to the non-stressed group (M= 588.874, SD= 101.575). Both groups had similar accuracy in all the conditions. When comparing the three attention network scores, no significantdifference was found in either group. However, in the stressed group, there was a significant beneficial relationship between the alerting and orienting networks (p=.006) and a high negative correlation between the alerting and executive control networks (p=.028). No significant correlation was found between the attention networks in the non-stressed group. Copyright©2024 by authors, all rights reserved.
Keywords: Attention Network; Chronic Stress; Neurodevelopmental Disorders; Typical Development